Biocompatibility and cyclic fatigue response of surface engineered Ti6Al4V femoral heads for hip-implant application. Issue 5 (1st March 2021) - Samanta, Aniruddha; Rane, Ramkrishna; Jhala, Ghanshyam; Kundu, Biswanath; Datta, Susmit; Ghosh, Jiten; Joseph, Alphonsa; Mukherjee, Subroto; Roy, Sandipan; Mukhopadhyay, Anoop Kumar
Abstract: A major problem with femoral head (FH) for hip implant (HI) applications is that it often fails in service. As a result, revision surgery becomes a must. The related trauma is tremendous for the patient, especially the aged ones. This also implies additional expenses. Keeping these aspects of the problem in view, here we report the development of wear, corrosion and fatigue resistant Ti6Al4V alloy based FH; by a duplex surface engineering (DSE) technique. Thus, the DSE based FHs are developed by a novel combination of plasma nitriding (PN) and Ti/TiN multilayer coating (MLC). The MLCs are formed by magnetron sputtering technique. The Ti6Al4V based FHs are called Ti. The only plasma nitrided FHs are called TiPN. The DSE based FHs are called TiPNML. The corrosion resistances are studied in hank's solution. The sliding wear resistance is studied in simulated body fluid (SBF). The biocompatibilities are studied by the standard MTT assay technique. The cyclic fatigue resistance behaviour up to one million walking cycles is studied in SBF in a HIP simulator with the UHMWPE acetabular cups used as the counter bodies in articulation. The results of the corrosion, biocompatibility, wear, and cyclic fatigue resposnses clearly reveal that the performances of the TiPNML and TiPN FHs are much better than that of the Ti based FHs. The reasons behind such spectacular improvement in biocompatibility as well as corrosion, wear and fatigue resistance are explained in terms of the prevalent phases, microstructural factors, wear mechanisms and surface roughness. The implications of the current results in terms of futuristic FH developments for HI applications are discussed. Such futuristic FH development could provide better HI. These prospects would minimize HI failure and hence, revision surgeries. Thus, the related trauma for numerous patients; especially the aged ones; could be significantly reduced.